2018
DOI: 10.1108/tr-10-2017-0155
|View full text |Cite
|
Sign up to set email alerts
|

Cruise tourism: social media content and network structures

Abstract: Purpose The purpose of this paper is to present knowledge acquired through examining three cruise lines’ social media strategies over a three-year period, analyzing the network structures involved and demonstrating the value of the STAR (storytelling, triggers, amusement and reaction) model for enhancing social media activity. Design/methodology/approach This study gathered data from three cruise lines’ official websites and Facebook and Twitter accounts, examining variables such as internet presence, engage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 46 publications
0
20
0
3
Order By: Relevance
“…With the development of ICT and IoT, AI has great impacts on tourism, such as understanding visitor behavior [18,44], suggesting personalized tourism route recommendation (Zheng and Liao [38]), and enhancing tourism marketing [23]. Although embracing autonomous vehicle in contemporary urban tourism still faces great challenges, the technology is hailed as an innovation that will drastically change urban mobility and personal travel behaviors [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of ICT and IoT, AI has great impacts on tourism, such as understanding visitor behavior [18,44], suggesting personalized tourism route recommendation (Zheng and Liao [38]), and enhancing tourism marketing [23]. Although embracing autonomous vehicle in contemporary urban tourism still faces great challenges, the technology is hailed as an innovation that will drastically change urban mobility and personal travel behaviors [30].…”
Section: Discussionmentioning
confidence: 99%
“…Social media has become increasingly important for museums to attract young people, directly communicate with users and build long-term relationships with visitors [21][22][23]. For example, Dutch museums are curating online presence on Twitter, LinkedIn, Instagram and Facebook to promote their offline businesses [3].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the destination Turkey [39], interactions with hoteliers appear to yield higher engagement, as do websites with multimedia content. Where there are story narratives, as in the case of cruise liners, the appeal to luxury travelers tends to be greater too [40]. Young adults using Facebook prefer information rather than emotional appeal.…”
Section: Findings and Analysismentioning
confidence: 99%
“…Moreover, posts that seek to encourage CSR practices recorded the highest level of customer engagement of the CSR-related posts. An assessment of social media engagement was also conducted by Tiago et al [40] in their analysis of luxury cruise ships. From their analysis, they showed that to achieve a content-oriented business strategy, these businesses need to adopt a social media approach that shares rich multimedia content across multiple platforms.…”
Section: Website User Interactions Turkeymentioning
confidence: 99%
“…It not only helps in business management but is also able to change the attitudes and needs of consumers. Many organizations use social media, transferring through storytelling, to refute, transfer and transfer emotionally [9].…”
Section: Introductionmentioning
confidence: 99%